Treatment of hind limb ischemia using angiogenic peptide nanofibers. (August 2016) - Kumar, Vivek A.; Liu, Qi; Wickremasinghe, Navindee C.; Shi, Siyu; Cornwright, Toya T.; Deng, Yuxiao; Azares, Alon; Moore, Amanda N.; Acevedo-Jake, Amanda M.; Agudo, Noel R.; Pan, Su; Woodside, Darren G.; et al.
Abstract: For a proangiogenic therapy to be successful, it must promote the development of mature vasculature for rapid reperfusion of ischemic tissue. Whole growth factor, stem cell, and gene therapies have yet to achieve the clinical success needed to become FDA-approved revascularization therapies. Herein, we characterize a biodegradable peptide-based scaffold engineered to mimic VEGF and self-assemble into a nanofibrous, thixotropic hydrogel, SLanc. We found that this injectable hydrogel was rapidly infiltrated by host cells and could be degraded while promoting the generation of neovessels. In mice with induced hind limb ischemia, this synthetic peptide scaffold promoted angiogenesis and ischemic tissue recovery, as shown by Doppler-quantified limb perfusion and a treadmill endurance test. Thirteen-month-old mice showed significant recovery within 7 days of treatment. Biodistribution studies in healthy mice showed that the hydrogel is safe when administered intramuscularly, subcutaneously, or intravenously. These preclinical studies help establish the efficacy of this treatment for peripheral artery disease due to diminished microvascular perfusion, a necessary step before clinical translation. This peptide-based approach eliminates the need for cell transplantation or viral gene transfection (therapies currently being assessed in clinical trials) and could be a more effective regenerative medicine approach to microvascular tissue engineering.